Modeling of Dolichol Mass Spectra Isotopic Envelopes as a Tool to Monitor Isoprenoid Biosynthesis . Issue 2 (6th April 2017) - Jozwiak, Adam; Lipko, Agata; Kania, Magdalena; Danikiewicz, Witold; Surmacz, Liliana; Witek, Agnieszka; Wojcik, Jacek; Zdanowski, Konrad; Pączkowski, Cezary; Chojnacki, Tadeusz; Poznanski, Jaroslaw; Swiezewska, Ewa
Abstract : A new method enables quantitative analysis of the contributions of the MVA and MEP pathways to generating isoprenoids. Abstract: The cooperation of the mevalonate (MVA ) and methylerythritol phosphate (MEP ) pathways, operating in parallel in plants to generate isoprenoid precursors, has been studied extensively. Elucidation of the isoprenoid metabolic pathways is indispensable for the rational design of plant and microbial systems for the production of industrially valuable terpenoids. Here, we describe a new method, based on numerical modeling of mass spectra of metabolically labeled dolichols (Dol s), designed to quantitatively follow the cooperation of MVA and MEP reprogrammed upon osmotic stress (sorbitol treatment) in Arabidopsis ( Arabidopsis thaliana ). The contribution of the MEP pathway increased significantly (reaching 100%) exclusively for the dominating Dol s, while for long-chain Dol s, the relative input of the MEP and MVA pathways remained unchanged, suggesting divergent sites of synthesis for dominating and long-chain Dol s. The analysis of numerically modeled Dol mass spectra is a novel method to follow modulation of the concomitant activity of isoprenoid-generating pathways in plant cells; additionally, it suggests an exchange of isoprenoid intermediates between plastids and peroxisomes.